2021
DOI: 10.18697/ajfand.99.18910
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable consumption patterns of urban farmers in community gardens in Emfuleni local municipality, Gauteng province of South Africa

Abstract: Lack of adequate vegetable consumption may contribute to micronutrient deficiency especially in developing countries where low intake of nutrient-dense animal products is common. Despite growing evidence that vegetable consumption is of great importance, only about 25.6% South Africans consume sufficient vegetables per day. This research was carried out to investigate the vegetable consumption patterns of urban farmers in Emfuleni Local Municipality, South Africa. The objectives were to determine reasons why… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In four studies the highest intake or purchase of fruit, vegetables or combined FV was observed among men ( 28 , 35 , 40 , 48 ). No differences between men and women, neither for fruit, nor for vegetable consumption or purchase was observed in ten studies ( 29 , 32 , 42 , 50 , 53 , 55 , 57 , 60 , 62 , 73 ).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…In four studies the highest intake or purchase of fruit, vegetables or combined FV was observed among men ( 28 , 35 , 40 , 48 ). No differences between men and women, neither for fruit, nor for vegetable consumption or purchase was observed in ten studies ( 29 , 32 , 42 , 50 , 53 , 55 , 57 , 60 , 62 , 73 ).…”
Section: Resultsmentioning
confidence: 82%
“…Twenty studies examined the role of education ( 29 32 , 35 , 40 , 42 , 43 , 50 , 52 54 , 56 , 62 , 64 , 67 , 73 , 76 , 79 , 80 ). Fourteen of these studies found that the frequency and quantity of fruit, vegetable and/or combined FV consumption and purchase increased with higher level of education ( 30 32 , 40 , 43 , 50 , 53 , 54 , 62 , 64 , 67 , 73 , 79 , 80 ). The majority of these studies referred to positive associations between education and fruit consumption for men and women ( 30 , 31 , 43 , 54 , 64 , 67 , 73 , 79 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, the levels of availability, accessibility, and affordability of food within vulnerable communities is a big food security issue in SA. Advancing the arguments raised by Queenan et al [42] in research addressing food consumption patterns and sustainability, other scholars argue that socially, physically, and economically food security is designed to combat hunger and malnutrition, which are major development problems affecting health and well-being in SA [2,[72][73][74][75]. Supporting these research arguments, FAO confirms that the high levels of food insecurity are a major challenge to SA, especially within vulnerable communities [11,76,77].…”
Section: Food Production and Food Consumptionmentioning
confidence: 95%
“…The research findings underscore the significant link between food production capacity, poor food consumption patterns, and poor human and economic development levels emerge. Consequently, these underdevelopment trends are responsible for perpetuating poverty, malnutrition, unemployment, crime, and poor quality of life among the disadvantaged local communities [4,43,44,75,77,80]. In a recent specific study associated with sustainability and food production, Queenan [42] argued that food production and food consumption systems are facing growing challenges associated with the zero hunger SDG.…”
Section: Food Production and Food Consumptionmentioning
confidence: 99%